An Assessment of the Relative Importance of Criminal Justice Learning Objectives. Issue 1 (2nd January 2017) - Baker, William M.; Holcomb, Jefferson E.; Baker, Daniel B.
Abstract : This study examines the relative importance of the different learning objectives for criminal justice education as identified by the Academy of Criminal Justice Sciences (ACJS). Three different populations (students, faculty, and professionals) completed a survey exercise in which they were required to rank order hypothetical job applicants who varied in competency on each of the ACJS learning objectives. In addition, students completed the same exercise pre- and post-completion of their required internship to determine if experience in the field affected their responses. Conjoint analysis was used to identify the relative importance of different learning objectives. While results indicate some similarities in responses across all three populations, several interesting differences were observed, and these may have important curricular implications for criminal justice programs.